2008
DOI: 10.1002/pbc.21600
|View full text |Cite
|
Sign up to set email alerts
|

Delays in diagnosis and treatment among children and adolescents with cancer in Canada

Abstract: Patient and referral delays were the longest time segments influencing timely diagnosis. Differences in delays were observed across age groups, cancer types and geographical regions. There was a significant trend for decreasing delays to diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
116
8
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(153 citation statements)
references
References 19 publications
23
116
8
6
Order By: Relevance
“…The short total delay reported from South-Africa could be a reflection of the superior infrastructure and health-care system in the country and is similar to total delays found in high-income countries, such as Canada which also has a median total delay of 34 days. [15][16][17][18] Health-care system delay in our study was significantly longer than patient delay. This is unlike what has been reported by the Nigerian study where patient delay was longer than health-care system delay as well as the Burkitt lymphoma study in Western Kenya.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The short total delay reported from South-Africa could be a reflection of the superior infrastructure and health-care system in the country and is similar to total delays found in high-income countries, such as Canada which also has a median total delay of 34 days. [15][16][17][18] Health-care system delay in our study was significantly longer than patient delay. This is unlike what has been reported by the Nigerian study where patient delay was longer than health-care system delay as well as the Burkitt lymphoma study in Western Kenya.…”
Section: Discussionmentioning
confidence: 68%
“…Although the total delay figures are similar to findings in Nigeria where median total delay was 109 days, our figures are longer than what has been reported in other studies done in Africa. [15][16][17][18] A study done in Western Kenya and Uganda, specifically looking at Burkitt lymphoma, reported total delays of 12.1 and 12.9 weeks respectively. This is shorter than what we found though close to what we found in our Non-Hodgkin lymphoma patients who had a mean total delay of 73 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] However, available information on the correctness of this assumption is insufficient, as studies on PSI in children with brain tumors suffer from low patient numbers, retrospective design, heterogeneity of patient, disease, and treatment characteristics, and lacking outcome data. [4][5][6][7][8][9][10][11][15][16][17][18][19][20][21][22][23][24] To study the association of the PSI with disease stage at diagnosis as well as tumor control and survival outcome, we analyzed prospectively collected data on 224 homogeneously treated patients. 3.…”
Section: -2mentioning
confidence: 99%
“…3 This can lead to prediagnostic symptomatic intervals (PSI) ('diagnostic time lags') in the range of several weeks to months. [4][5][6][7][8][9][10][11] The assumption that a longer PSI may result in a more advanced disease stage and/or have an adverse impact on tumor control, survival and/or neurological/neuropsychological/quality of survival outcome may lead to selfreproaches from parents and physicians and can result in accusations of medical malpractice. [12][13][14] However, available information on the correctness of this assumption is insufficient, as studies on PSI in children with brain tumors suffer from low patient numbers, retrospective design, heterogeneity of patient, disease, and treatment characteristics, and lacking outcome data.…”
Section: -2mentioning
confidence: 99%